EPIDEMIOLOGICAL STUDY OF HEMATOLOGICAL CHANGES IN PRIMARY MALIGNANT BONE TUMOR IN ADULT AND PEDIATRIC AT BLOOD DISEASES CANCER OF THE SULAYMANIYAH PROVINCE OF IRAQI KURDISTAN (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Primary Malignant Bone tumor in pediatrics are rare tumors that affect bones in children and adolescents, known (Sarcoma ), common type sarcoma are osteosarcoma commonly affect appendicular skeleton (long bones) and Ewing sarcoma that effect axial skeleton(flat bone) . Patients and methods :This study included 91 pediatric patient (0-18) years ages of both gender with primary malignant bone cancer ,registered and diagnosed in Hiwa Cancer Hospital\ Sulaymaniyah city, from the time period (2016-2019) to study the characteristics of patients: age, gender, symptoms and signs, clinical stages, primary site , and metastatic site of bone cancer. Results: Male showed a significantly higher incidence than females, with a male-female ratio of 1.2:1 and rural population almost all parts of the country had highest incidence . Ewing sarcoma 1st most common type 53% with mean age 12.8 years, area involved 59% in appendicular skeleton and 40% in axial skeleton, 26% of patient had metastasis at diagnosis, mostly bone, lung and bone marrow , symptoms that might aid diagnosis ES included early local volume increase, neurological symptoms and the presence of fever. Osteosarcoma 2nd most common type 46% with a mean age of 15.7 years, were located 95% in appendicular skeleton and 4% in axial skeleton, 16% of patient had metastasis at diagnosis, mostly lung .Conclusion: In this study, Ewing sarcoma were the first most common type and osteosarcoma were second common type, with male predominance in both types. We haven’t stage I in ES . Adolescent age group with OS not ES observed taller in comparison with other OS age group at time of diagnosis correlated to pubertal skeletal growth as a risk factor.